Interpersonal autonomic synchrony and sexual satisfaction: A preliminary examination - B. Freihart; M. Sears; C. Meston (European Psychiatry, 2022)
Introduction A growing body of literature has increased our understanding of interpersonal autonomic synchrony (IAS), or exchanges across biological systems resulting in physiological covariation. While research suggests that IAS is more likely in relationships characterized by emotional intimacy, no research to date has examined the connection between IAS and the quality of sexual relationships.